A compact symmetric ejection from the low mass AGN in the LINER galaxy NGC 4293. Issue 4 (21st October 2022) - Yang, Xiaolong; Wang, Ruiling; Guo, Quan
ABSTRACT: We conducted a Very Long Baseline Array (VLBA) observation of the low mass active galactic nucleus (AGN) in galaxy NGC 4293 ( z = 0.003). The object is associated with a low-ionization nuclear emission-line region (LINER). Its black hole mass is estimated as ∼10 5 or ${\sim}10^7 \, M_\odot$ . The VLBA 1.5 GHz image shows an inverse symmetric structure with two discrete radio blobs separated by an angular distance of ∼120 mas, corresponding to ∼7 parsec. Furthermore, its integrated radio spectrum has a turnover at the frequency of ∼0.44 GHz. Based on the compactness and spectrum, the nuclear radio source in NGC 4293 belongs to a sample of (megahertz) peaked spectrum (PS/MPS) radio sources with compact symmetric morphologies. NGC 4293 has 1.4 GHz radio power of only ${\sim}10^{20}\, \mathrm{W\, Hz^{-1}}$ with the VLBA observation, which is consistent with local AGNs but lower than the current PS samples. One of the two blobs has a steep radio spectrum α = −0.62 ± 0.08 ( S ν ∝ ν +α ), while the other one has an inverted spectrum α = 0.32 ± 0.10. The VLBA 1.5 GHz luminosity ratio of the two blobs is 3.23 and both blobs show lateral-flowing structures where the hotspots reside at the edge of each radio lobe. This can be explained as jet interactions with dense circumnuclear medium. We estimate the black hole mass of NGC 4293 through the Fundamental Plane of black hole activity, which constrains the black hole mass to be ${\lesssim}10^6\, M_\odot$ . It supports that the object is a low-mass AGN and a potential candidate for accreting and ejecting IMBHs.